PENANGANAN HASIL PANENTANDAN BUAH SEGAR KELAPA SAWIT OLEH KOPERASI HARAPAN JAYA - Munawar Thoharudin; Fatkhan Amirul Huda; Tedi Suryadi (GoAcademica Research dan Publishing, 2020)
Oil palm is one of the commodities of plantation products which has an important role in economic activities in Indonesia. The existence of the Harapan Jaya cooperative is very helpful for the plasma farmers in the village who are not prosperous. In addition to being able to provide cooperative capital assistance, the role is to ensure that farmers 'harvests are sold every month, while other cooperatives are unable to provide certainty about the sale of farmers' harvested fruits. The aim of this study was to discuss the handling of yields of oil palm fresh fruit bunches by cooperative expectations. The research approach used in this study is a qualitative approach. The research was carried out in a village of prosperous hope cooperative units in a village that was not successful. Site selection is determined intentionally. Data collection is done by in-depth interviews and documentation. The variables in this study consisted of mechanisms for handling yields of fresh palm fruit bunches. The data analysis method used in this study is descriptive qualitative. Based on the results of the study, information was obtained regarding the problems faced by oil palm farmers, especially in villages that were not successful. The solution to overcome this problem is through 3 mechanisms for supplying fruit-bearing trucks, cooperating with several palm oil mills, selling FFB to factories at high prices, and ensuring that the plantation roads are feasible to pass.